New columns for architecture in reinforced concrete - Jolly Monge, David (Revista de la Construcción. Journal of Construction, 2017)
This paper concerns the provision of new architectural forms in reinforced concrete, obtaining volumes with a double curve surfaces at a reasonable cost, constructed using flexible formwork. Through design research (research by design) 8 types of columns made of in situ reinforced concrete are achieved. An architectonic element with optimal spatial quality and an organic form, with a surface not requiring another finish is the end in mind. The construction process is relatively simple given the results obtained and the construction of prototypes during building work on site opens up the possibility of using this technology on building sites everywhere reinforced concrete is available.